Статистична оптимізація частотно регульованих асинхронних електроприводів при скалярному керуванні - Шуруб, Ю.В. (Електротехніка і електромеханіка, 2017)
Разработана методика синтеза статистически оптимальных регуляторов асинхронных электроприводов с частотным скалярным управлением, работающих при стохастических моментах нагрузки. Определены оптимальные структуры регуляторов электроприводов такого класса в зависимости от вида случайных возмущений. На примере моделирования работы электропривода дробилки зерна показана эффективность фильтрации статистически оптимальным регулятором высокочастотных составляющих моментов нагрузки и повышение циклических показателей энергоэффективности электропривода, таких как цикловые КПД и коэффициент мощности. Розроблено методику синтезу статистично оптимальних регуляторів асинхронних електроприводів з частотним
скалярним керуванням, що працюють при стохастичних моментах навантаження. Визначені оптимальні структури регуляторів електроприводів такого класу в залежності від виду випадкових збурень. На прикладі моделювання роботи електроприводу дробарки зерна показано ефективність фільтрації статистично оптимальним регулятором
високочастотних складових випадкових моментів навантаження та підвищення циклових показників енергоефективності електроприводу, таких як циклові ККД та коефіцієнт потужності. Purpose. Working out of technique of synthesizing statistically
optimal controllers of induction electric drives with frequency
scalar control operating under stochastic loads. Methodology.
It is shown, that one of the ways of increasing the energy efficiency of induction electric drives at random changes of loads is
to create closed systems of electric drives with statistically optimal regulators that would take into account the stochastic nature of the disturbances and acted as filters of occasional high
frequency fluctuations. The structure of such controls depends
on the statistical characteristics of stochastic loads – correlation function and spectral density. In this mode, the minimum
loss in dynamic mode with random intensive changed loads is
provided by criterion of minimum mean square error of optimal
parameter control. In the case of frequency controlled electric
drive such a parameter is the optimum rotor flux. Results. The
optimal structures of regulators of electric drives under stochastic loads according to type of random disturbances are identified. Originality. The technique of statistically optimal synthesis
with feature of the expansion of a random process load on average, served as a useful signal, and high-frequency fluctuations
around the average value, served as barrier, is developed. Practical value. On an example of simulation of work of the electric
drive of a crusher of grain it is shown efficiency of a filtration by
statically optimal regulator of the high-frequency components of
random torques of load, reduction of dispersions of its outlet
parameters, increase of cyclic indicators of energy efficiency of
the electric drive, such as cyclic efficiency and power factor.